Cultural and semantic nature of the concept «horse» (Eurasian Journal of Philology Science and Education, 2020)
At the present time, scientists have fully approved that the training of horses was started in the Kazakh steppe. There is concrete evidence of this. And taming the horse increased the stage of cultural development. The Kazakh people cared about horses, which could be used when riding like transport, when you drink like kumys, when you eat like kazy. For this , they learned about the diseases of horses and knew the therapeutic effect, from early times, when medicine had not yet developed. We say kazakhs that “Born on a horse, lived on a horse”. There is have a reason. Riding horse, drinking koumiss, eating karta all this actions were reflected in the kazakh songs, proverbs, aphorisms and phraseological units, served as a revival of the vocabulary of the kazakh language. So many centuries have passed the Kazakhs developing urban culture, removed nomadic culture that lived by riding a horse. Grazing cattle was only the occupation for people. But the words associated with the horse did not go out of use. And helping to analyze and correctly use such words is the task of such scientists-correspondents like us. In this article we have tried to reveal that the Kazakh people with the help of a horse rose to the highest peaks of culture. In particular, with regard to horse breeds, we have shown that words have influenced the language of the nation, and the national code is related to the horse.